Gender variation in active mobility: experience from Johannesburg South Africa - Aderibigbe, Oluwayemi-Oniya; Gumbo, Trynos (Frontiers in Built Environment, 2025)
IntroductionGood public transport accessibility is often linked to increased active travel, yet Q6 gender differences in this area are relatively under-researched. Our study aimed to explore these gender variations in active mobility within Johannesburg, South Africa. To achieve this, we utilized a robust research design, collecting primary data through an online survey administered via Google Forms.MethodsA total of 425 structured questionnaires was distributed using a random sampling approach, with the survey being sent through email and social media platforms such as WhatsApp and Facebook. Respondents provided information on their socioeconomic characteristics, travel behaviours, and factors influencing their use of active travel. We employed the Likert scale method for response ranking and used the binary logistic model being a choice model to validate the Likert scale results and also explain reasons for respondents actions based on their choices.Results and discussionsOur findings indicated significant gender-based differences in both socio-economic and travel characteristics. Factors influencing active mobility for women, in particular, included, car ownership, income level, availability of pedestrian facilities, travel time, age, safety, and the condition of public transport. Based on these findings, we recommend that policymakers consider gender differences that support the use of active travel especially in the area of safety, as well as provision of specific public transport infrastructures to accommodate the needs of women in accordance to their age and life cycle in the study area.